Information processing. Unrecorded 12, 7 mm (0.5 in) wide magnetic tape for information interchange. 32 ftpmm (800 ftpi) NRZ1, 126ftpmm (3 200 ftpi) phase encoded and 356 ftpmm (9 042 ftpi), NRZ1. (31st January 1992) - British Standards Institution,
No abstract available